2014
DOI: 10.5901/jesr.2014.v4n6p183
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Cell Phones and Emotional Behaviour of Undergraduates in Nigerian Universities

Abstract: The study examined students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A high percentage of the students (32.3%) believe that phone can be a source of distraction as against (18.5%) who believes that it can be educative. The results gotten fron Amali et al [16] and Ajihadun et al [2] also revealed that smartphones can be a source of distraction during lectures and at night during sleep respectively, It can infact lead to addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high percentage of the students (32.3%) believe that phone can be a source of distraction as against (18.5%) who believes that it can be educative. The results gotten fron Amali et al [16] and Ajihadun et al [2] also revealed that smartphones can be a source of distraction during lectures and at night during sleep respectively, It can infact lead to addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Instructions and messages are now received promptly and immediately. In fact, it has made the world to function as a global village [2].…”
Section: Introductionmentioning
confidence: 99%